Thing Knowledge : A Philosophy of Scientific Instruments - Baird, Davis (Book collections on Project MUSE., 2004)
Western philosophers have traditionally concentrated on theory as the means for expressing knowledge about a variety of phenomena. This absorbing book challenges this fundamental notion by showing how objects themselves, specifically scientific instruments, can express knowledge. As he considers numerous intriguing examples, Davis Baird gives us the tools to "read" the material products of science and technology and to understand their place in culture. Making a provocative and original challenge to our conception of knowledge itself, Thing Knowledge demands that we take a new look at theories.